On leap indices of CNCk[n] by using line operator on its subdivision. (17th February 2021) - Zahid, Zohaib; Asif, Fatima; Khalaf, Abdul Jalil M.; Farahani, Mohammad Reza
Abstract: Molecular descriptors also known as topological indices are numeric quantities which characterize its topology and some properties of molecular graph. The 2-distance degree of a vertex u in a graph G is equal to the number of its second neighbors and topological indices based on second neighbors of end vertices are named as leap indices. Leap indices have gained attention of many researchers. Therefore in this paper, we find some exact values for the leap Zagreb indices and leap hyper-indices of carbon Nanocones.